A 3D printed nano bone matrix for characterization of breast cancer cell and osteoblast interactions. (24th June 2016) - Zhu, Wei; Castro, Nathan J; Cui, Haitao; Zhou, Xuan; Boualam, Benchaa; McGrane, Robert; Glazer, Robert I; Zhang, Lijie Grace
Abstract: Bone metastasis is one of the most prevalent complications of late-stage breast cancer, in which the native bone matrix components, including osteoblasts, are intimately involved in tumor progression. The development of a successful in vitro model would greatly facilitate understanding the underlying mechanism of breast cancer bone invasion as well as provide a tool for effective discovery of novel therapeutic strategies. In the current study, we fabricated a series of in vitro bone matrices composed of a polyethylene glycol hydrogel and nanocrystalline hydroxyapatite of varying concentrations to mimic the native bone microenvironment for the investigation of breast cancer bone metastasis. A stereolithography-based three-dimensional (3D) printer was used to fabricate the bone matrices with precisely controlled architecture. The interaction between breast cancer cells and osteoblasts was investigated in the optimized bone matrix. Using a Transwell ® system to separate the two cell lines, breast cancer cells inhibited osteoblast proliferation, while osteoblasts stimulated breast cancer cell growth, whereas, both cell lines increased IL-8 secretion. Breast cancer cells co-cultured with osteoblasts within the 3D bone matrix formed multi-cellular spheroids in comparison to two-dimensional monolayers. These findings validate the use of our 3D printed bone matrices as an in vitro metastasis model, and highlights their potential for investigating breast cancer bone metastasis.